2017
DOI: 10.1007/s12253-017-0347-7
|View full text |Cite
|
Sign up to set email alerts
|

Invitro Evaluation of Torin2 and 2, 6-Dihydroxyacetophenone in Colorectal Cancer Therapy

Abstract: Colorectal cancer (CRC) is one of the most prevalent cancers diagnosed worldwide. Despite recent advances, resistance to cytotoxic and targeted therapy remains one of the greatest challenges in long-term management of colorectal cancer therapy. Recently established role of mTOR signaling in proliferation of CRC has incited for evaluation of mTOR kinase specific inhibitors in CRC therapy. Second generation mTOR kinase inhibitors including Torin2 has demonstrated efficient anticancer properties against variety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Chang et al have also conducted cell proliferation assays with human synovial cell lines [ 62 ]. The fluorescent microscopic technique has been used to detect morphological changes upon treatment with various polyphenols in various cancer and RA cell lines [ 63 , 64 ]. It has become an excellent technique for cell and tissue imaging and to observe biological processes.…”
Section: In Vitro Test With Polyphenolsmentioning
confidence: 99%
“…Chang et al have also conducted cell proliferation assays with human synovial cell lines [ 62 ]. The fluorescent microscopic technique has been used to detect morphological changes upon treatment with various polyphenols in various cancer and RA cell lines [ 63 , 64 ]. It has become an excellent technique for cell and tissue imaging and to observe biological processes.…”
Section: In Vitro Test With Polyphenolsmentioning
confidence: 99%
“…Another possibility is that Torin-2 suppresses UHRF1 expression independently of mTORC1 [ 118 ]. Torin-2 treatment led to growth inhibition and the induction of apoptosis in colorectal [ 121 ], small-cell lung cancer, and non-small-cell lung cancer [ 122 ], highlighting the potential of Torin-2 as an anti-cancer agent. Moreover, a recent study reported that UHRF1 silencing could increase the radiosensitivity of ESCC (esophageal squamous cell carcinoma) through the inhibition of the PI3K/Akt/mTOR signaling pathway [ 123 ].…”
Section: Synthetic Molecules Targeting Uhrf1mentioning
confidence: 99%
“…Besides, both arbutin [62] and its derivatives 6'-p-coumarylarbutin [63] have strong inhibitory effect on human tyrosinase activity and arbutin is commonly used as a powerful skin whitening agent in cosmeceuticals [64]. Also, 2',6'-dihydroxyacetophenone [65] is a bioactive phenolic acid with anticancer properties. In addition, camelliaside A can relieve burns via inhibiting inflammation and enhancing collagen synthesis [66], and shows obvious neuroprotective activity [67].…”
Section: Plos Onementioning
confidence: 99%